2017
DOI: 10.1063/1.5016163
|View full text |Cite
|
Sign up to set email alerts
|

A note on the Duffin-Kemmer-Petiau equation in (1+1) space-time dimensions

Abstract: In the last years several papers addressed the supposed spin-1 sector of the massive Duffin-Kemmer-Petiau (DKP) equation restricted to (1+1) space-time dimensions. In this note we show explicitly that this is a misleading approach, since the DKP algebra in (1+1) dimensions admits only a spin-0 representation. Our result also is useful to understand why several recent papers found coincident results for both spin-0 and spin-1 sectors of the DKP theory in (3+1) dimensions when the dynamics is restricted to one s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In addition, spin-0 system of the DKP equation in the presence of Gödel-type space-time [16] and in a topologically trivial space-time background [17], and the DKP oscillator in a Gödel-type space-time [18] were studied. The equivalency of the spin-one and spin-zero representation of the DKP equation in one dimension was discussed by Lunardi in [19]. Some inaccurate discussion in the literature based on the DKP equations in one dimension was pointed out by Chargui in [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, spin-0 system of the DKP equation in the presence of Gödel-type space-time [16] and in a topologically trivial space-time background [17], and the DKP oscillator in a Gödel-type space-time [18] were studied. The equivalency of the spin-one and spin-zero representation of the DKP equation in one dimension was discussed by Lunardi in [19]. Some inaccurate discussion in the literature based on the DKP equations in one dimension was pointed out by Chargui in [20].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative way to overcome this problem is to evaluate the DKP equation in the lower dimensions in order to obtain the behavior of semi-classical and quantum gravity. In the literature, we find many studies related to the general relativity in (1 + 1)-dimensions [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Boutabia-Chéraitia et al [11] presented a calculation of the Green's function of the DKP equation in the case of scalar and vectorial particles interacting with a square barrier potential and its relation to the KG equation. Recently, Lunardi [12] has shown that the supposed spin-1 sector of the theory restricted to (1 + 1) space-time dimensions actually is unitarily equivalent to its spin-0 sectors. This work is organized as follows: In Section 2, we give the DKP equation for the spin-0 with 5 × 5 beta matrices and 10 × 10 beta matrices for the spin-1.…”
Section: Introductionmentioning
confidence: 99%